Música popular e currículo: reflexões sobre as mensagens ouvidas pelos alunos e suas possíveis implicações em relação ao currículo oficial - FERREIRA NETO, Anthymio Wanzeller (Universidade Federal do Oeste do Pará, 2021)
This research aims to reflect on the messages conveyed by the popular songs of consumption offered by the Cultural Industry as a possible voice of a hidden curriculum that arises from its insertion within the school space through the students. Based on the idea of a musical scene, we sought to understand how these musical scenes can contribute to the formation and / or sociocultural deformation of the students, taking as their starting point the citizen formation defended by the official school curriculum. For this approach, we take as reference the Critical Theories (ADORNO 1995, 2005), Theory of communication (BESSA 2006, SILVA 2011, JANOTTI JR and Sá 2013) and on musical relations in everyday life (BRÉCIA 2003, LOUREIRO 2010; BOZZANO , FRENDA and GUSMÃO 2013). They have as central questions: What do teenagers hear in the music scenes inside the school? What is the most heard message in this scene? How can this message be based on a hidden curriculum in relation to the citizen education defended by the school? Basically what matters are the messages heard and disseminated by the lyrics of the songs to the adolescents who participated in this study and who arrive through the media to the same media. The most present musical Scene within the school with which the adolescents identify themselves. The learning situations that these musical scenes can provide in front of the programming of the messages of the song heard. The study tends to contribute to a differentiated view on the role of popular music of media consumption in the daily life of the school and the processes of socio-cultural appropriation systematized by the hidden curriculum from the messages heard in the musical scenes existing in the school context.